PQ-LEACH: A novel post-quantum protocol for securing WSNs communication - Shaykhah S Aldosari; Layla S Aldawsari (International Journal of Engineering Business Management)
Ensuring the confidentiality of communication is of paramount significance. Traditionally, cryptographic practices for Wireless Sensor Networks (WSN) have been primarily based on classical cryptography like RSA and Elliptic Curve, which are potentially susceptible to cyber attacks from future quantum computers with enough computing power. To ensure the protection and safety of inter-node communication in WSNs, it becomes imperative to employ a Post-Quantum Cryptography (PQC) algorithm. This paper presents post-quantum low-energy adaptive clustering hierarchy (PQ-LEACH), an advanced secure wireless communication protocol based on the LEACH protocol. By integrating post-quantum cryptography, specifically Kyber’s key encapsulation method, and a key update system, PQ-LEACH effectively enhances the security of communication and mitigates various WSN attacks. Additionally, a comprehensive performance analysis of PQ-LEACH, including its impact on network energy efficiency and longevity, is conducted. The results demonstrate the trade-offs between enhanced security measures and operational performance, providing critical insights for the deployment of secure and efficient WSNs in a quantum-threatened landscape.